Art of teaching and the crossroads with the XV Meeting On Research In School (Research, Society and Development, 2019)
This article aims to reflect on the art of teaching life and the crossings from the XV Meeting on Research in School in Porto Alegre, Rio Grande do Sul, Brazil. In this context, teaching is present daily in the routine of each individual, however, the school, with the help of the teacher, plays a fundamental role in the construction of personal and professional training of the human being. Under this threshold, educational transformations related to the teaching and learning process are observed. These changes can be attributed to the pedagogical actions promoted by intrinsic or extrinsic movements exercised by teachers. Several are the stories that move new actions and that result in memorable teaching experiences in the school environment. The XV Meeting on Research in School was attended by the school community in its wide diversity, with the art of teaching and learning enriched by the participants' reports. This is a reflective, descriptive and exploratory article that invites the reader to reflect on the educational aspects and discussions present at the XV Meeting on Research in School in Porto Alegre, Rio Grande do Sul, Brazil. The event sparked a wide and rich discussion about teaching and learning practices in the classroom, as well as the construction of being a teacher in primary and higher education. This meeting provoked the awakening of change through an education linked to art, articulated to an innovative view on teaching practice and the value of teaching.